Collaborative Governance Strategy In Accelerating Vaccination Through Vaksinasi Merdeka (Independence Vaccination) Innovation Program In Jakarta City Area - Rahmawati, Devie; Anindhita, Wiratri; Imran, Mohammad Fadil; Bachtiar, Youna Chatrine; Abdullah, Zulhamri Bin; Ramadhan, Muhammad Zaky; Lumakto, Giri (International Journal of Artificial Intelligence Research, 2024)
Polda Metro Jaya with the Vaksinasi Merdeka (independent vaccination) innovation program has initiated a community-based and collaborative governance strategy where Polda Metro Jaya team gone directly to the community to study, innovate and implemented a better vaccination program, that proven to be more effective and efficient than any other vaccination program. The use of ethnographic study for ten months research, found that this success of the program started with the data science approach that resulted with a vaccination innovation program design that are closer and familiar to the people in the DKI Jakarta area.